The phenomenon of nomophobia behaviour among students: a perspective of interpersonal communication - Oknita, Oknita; Lahmuddin, Lahmuddin; Kholil, Syukur (Faculty of Communications Science, Dr. Soetomo University, 2023)
This research aims to analyse the phenomenon of nomophobia behaviour and the effectiveness of interpersonal communication and identify prevention measures among students at the State Islamic University of Lhokseumawe. This is a qualitative research study. The data collection techniques used are interviews, observation, and document study. Next, the data is processed and analysed using Miles & Huberman's analysis model, which involves data reduction, data display, and conclusion drawing. This research uses source, method, and time triangulation techniques to obtain relatively valid conclusions. The research findings indicate that the phenomenon of nomophobia behaviour among students at IAIN Lhokseumawe is characterised by (1) ignoring conversation partners (phubbing), (2) feeling anxious when without a smartphone, (3) spending more than 7-12 hours a day on their smartphone, (4) preferring to be alone or isolated, (5) prioritising buying gadgets over other things, and (6) repeatedly checking their smartphone. The effectiveness of interpersonal communication of people living with nomophobia is measured using the humanistic approach proposed by Devito, which includes (1) openness, (2) empathy, (3) positive attitude, and (4) supportive attitude. Prevention measures for overcoming nomophobia behaviour include (1) parental supervision, (2) strong individual willpower, (3) time management, and (4) engaging in positive activities or utilising personal talents. The research discovered a novel finding that nomophobia behaviour has become a new norm and that there needs to be ethics in interpersonal communication.